E-Commerce, The Digital Trend in Transaction - Astuti, Wati Aris; Ramayani, M A (Journal of Business and Behavioural Entrepreneurship, 2021)
E-commerce is one of the most important media that companies always used today. Therefore, the development of business today is very influential in e-commerce. The purpose of this research is to find out how much the influence of e-commerce media use in the business field today as a practical online promotion media for buying and selling a product. The method used in this research is a descriptive method with a qualitative approach and data collection techniques in the form of a literature study. Research informants in this study have 2 informants namely Internal Public (Employees) and External Public (Consumers). The results of this study are the importance of the development of technology and information at this time. In this case, e-commerce makes it easy for a variety of human activities which is easily done anywhere and by anyone in meeting their needs and desires. With e-commerce, entrepreneurs will also find it easier to get profits because it can increase business connections and expand global networks that spread to all circles.